ROS1-Rearranged Lung Adenocarcinoma: From Molecular Genetics to Target Therapy - Ugo Testa; Germana Castelli; Elvira Pelosi (Onco, 2023)
Non-small-cell lung cancer (NSCLC) is a heterogeneous group of diseases accounting for 80–85% of lung cancers. A molecular subset of NSCLC (1–2.5%) harboring molecular rearrangements of the tyrosine kinase gene ROS1 is defined as ROS1-positive and is almost exclusively diagnosed in patients with lung adenocarcinoma histology, predominantly nonsmokers. ROS1 is constitutively activated by molecular rearrangements and acts as a main driver of lung carcinogenesis. These findings have provided a strong rationale for the clinical use of tyrosine kinase inhibitors that target ROS1; these inhibitors block ROS1-positive NSCLC and provide clinical benefit. Crizotinib was introduced as a first-line treatment for ROS1-positive NSCLCs, with 75–80% of patients responding and a PFS of about 20 months. More recently developed ROS1-TKIs, such as entrectinib, lorlatinib, taletrectinib, repotrectinib and NVL-520, are active against some resistant ROS1 mutants appearing during crizotinib therapy and more active against brain metastases, frequent in ROS1-positive NSCLC. The development of resistance mechanisms represents a great limitation for the targeted treatment of ROS1-positive NSCLCs with TKIs.